The Evolution of Reforestation in Brazil - Carlos Bacha (European Regional Science Association (ERSA), 2003)
This paper analyzes the evolution of reforestation in Brazil and makes an evaluation of federal government policies used to stimulate that activity. Despite the huge increase of reforestation areas in Brazil since the 1970s, what put up Brazil as the sixth large country with reforested areas, a scarcity of roundwood from reforested areas is happing in that country during the first decade of the 21st century. Federal government implemented three programs to foster the reforestation in Brazil during the 1960s, 1970s and 1980s. However, nothing was implemented during the 1990s, when demand of roundwood increased, but not its production. This paper analyzes those programs, using a traditional cost-benefit approach. The results of that evaluation are used to suggest new federal government policies to foster the enlargement of reforestation in segments where price mechanism has not working well.
Keywords: 330